Wood to Energy: Woody Biomass Basics - Jessica Tomasello; Lauren McDonell; Martha C. Monroe; Annie Oxarart (EDIS)
FOR-221, a 4-page illustrated fact sheet by Jessica Tomasello, Lauren McDonell, Martha C. Monroe, and Annie Oxarart, is part of the Wood to Energy series. It discusses non-renewable and renewable energy sources in general and woody biomass as a source of renewable energy. Includes references. Published by the UF School of Forest Resources and Conservation, June 2009.